Investigation of the Relationship between the AKT1 rs1130233 (G>A) Polymorphism and the Risk of Breast Cancer in Iraqi Women - M. Hade, Istikrar (Asian Pacific Journal of Cancer Biology, 2025)
Background: Genetic changes like as single-nucleotide polymorphisms (SNPs) in the AKT1 gene have been linked to carcinogenesis. The AKT kinases are important regulators of cell survival, proliferation, and apoptosis, and evidence suggests that the rs1130233 (G>A) SNP affects AKT1 expression and leads to breast cancer. The aim of this study was to investigate the association between the AKT1 rs1130233 (G>A) single-nucleotide polymorphism and the susceptibility to breast cancer in Iraqi women, and to evaluate its potential role as a diagnostic biomarker. Methods: A case-control study was carried out on 200 people, comprising 100 breast cancer patients and 100 healthy controls. Genomic DNA was isolated from peripheral blood samples and genotyped using the polymerase chain reaction (PCR) technique. Results: The wild-type homozygous GG genotype was much more common in healthy women (79%) than in patients (30%), indicating a preventive function against breast cancer. In contrast, the heterozygous GA (30%) and mutant homozygous AA (40%) genotypes were more common among patients, indicating a higher risk of developing breast cancer. Allele frequency analysis revealed that the A allele was linked to a greater incidence of breast cancer (p < 0.01). Conclusion: The AKT1 rs1130233 (G>A) polymorphism is strongly linked to breast cancer risk in Iraqi women. The G/G genotype may provide protection, while the A allele increases susceptibility. These findings emphasize the potential use of the AKT1 polymorphism as a diagnostic biomarker, while further validation in larger and more diverse populations is suggested.